Rekonstruksi Pemaknaan Hak Masyarakat Hukum Adat (MHA) atas Hutan Adat - Wihelmus Jemarut; Kornelia Webliana B (Jurnal Interpretasi Hukum, 2024)
This article aims to analyze the rights of Customary Law Communities (MHA) over Customary Forests. The research method used is normative with a conceptual and legislative approach. The concept or theory used is the property rights theory. The results of the study indicate that MHA rights in laws and regulations only include access rights, rights to collect results, and management rights. Based on the property right theory, what MHA does not have is the right to exclude - the right to determine who has access rights or the right to determine the participation/exclusion of other parties in the area - and the right to sell or transfer rights. The researcher recommends that the only MHA rights that need to be revoked by the state in controlling customary forests are the right to sell or the right to transfer.